FcγRIIb and BAFF Differentially Regulate Peritoneal B1 Cell Survival - Amezcua Vesely, Maria Carolina (2012)
B1 cells produce most natural Abs in unimmunized mice and play a key role in the response to thymus-independent Ags and microbial infection. Enlargement of B1 cell number in mice is often associated with autoimmunity. However, the factors that control peripheral B1 cell survival remain poorly characterized. Mice lacking the inhibitory receptor FcgRIIb exhibit a massive expansion in peritoneal B1 cells, implicating this receptor in B1 cell homeostasis. In this study, we show that peritoneal B1 cells express the highest levels of FcgRIIb among B cell subsets and are highly susceptible to FcgRIIb-mediated apoptosis. B1 cells upregulate FcgRIIb in response to innate signals, including CpG, and the B cell homeostatic cytokine BAFF efficiently protects activated B1 cells from FcgRIIb-mediated apoptosis via receptor downregulation. BAFF-transgenic mice manifest an expansion of peritoneal B1 cells that express lower levels of FcgRIIb and exhibit reduced susceptibility to apoptosis. Whereas both peritoneal B1 cells from wild-type and BAFF-transgenic mice immunized with CpG exhibit an increase in FcgRIIb levels, this change is blunted in BAFF-transgenic animals. Our combined results demonstrate that FcgRIIb controls peritoneal B1 cell survival and this program can be modulated by the BAFF signaling axis.